Prevalence and Socio-Demographic and Hygiene Factors Influencing Impetigo in Saudi Arabian Children: A Cross-Sectional Investigation - Aleid AM; Nukaly HY; Almunahi LK; Albwah AA; AL- Balawi RMD; AlRashdi MH; Alkhars OA; Alrasheeday AM; Alshammari B; Alabbasi Y; Al Mutair A (Dove Medical Press, 2024)
Ali M Aleid,1 Houriah Y Nukaly,2 Lina K Almunahi,3 Ahood A Albwah,4 Rahaf Masoud D AL- Balawi,5 Mohsen H AlRashdi,6 Ola A Alkhars,7 Awatif M Alrasheeday,8 Bushra Alshammari,9 Yasmine Alabbasi,10 Abbas Al Mutair11 1Dermatology Department, Ministry of Health, Riyadh, Saudi Arabia; 2Medicine Program, Batterjee Medical College, Jeddah, 21442, Saudi Arabia; 3College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 4College of Medicine, King Khalid University, Abha, Saudi Arabia; 5Faculty of Medicine, University of Tabuk, Tabuk, Saudi Arabia; 6Department of Medicine and Surgery, Umm Al Qura University, Alqunfidah, Makkah, Saudi Arabia; 7Pediatric Department, King Faisal General Hospital, Jeddah, Saudi Arabia; 8Nursing Administration Department, College of Nursing, University of Hail, Hail, 2440, Saudi Arabia; 9Medical Surgical Nursing Department, College of Nursing, University of Hail, Hail, 2440, Saudi Arabia; 10Department of Maternity and Pediatric Nursing, College of Nursing, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 11Department of Medical-surgical Nursing, Princess Nourah bint Abdulrahman University, Riyadh, Saudi ArabiaCorrespondence: Yasmine Alabbasi, Department of Maternity and Pediatric Nursing, College of Nursing, Princess Nourah bint Abdulrahman University, P.O. Box 84428, Riyadh, 11671, Saudi Arabia, Email yaalabbasi@pnu.edu.saPurpose: To determine the prevalence of impetigo among children in Saudi Arabia as well as to identify socio-demographic factors associated with impetigo.Methods: This cross-sectional study conducted in Saudi Arabia examined impetigo prevalence and associated factors among children aged 2 to 15. Data collection occurred between June 2022 and November 2023, involving structured interviews with the parents or legal guardians of the participating children. A pre-designed questionnaire was used, which included questions related to personal hygiene practices (such as, frequency of handwashing, bathing routines, and use of communal facilities), environmental conditions, and the child's impetigo diagnosis history.Results: The study encompassed a total of 1200 participants, with a predominant representation of female (79.3%). Participants exhibited a diverse age distribution, with the highest proportion falling within the 18- 24 age group (33.7%). Importantly, a statistically significant association was identified between the occurrence of impetigo in children and their personal hygiene scores (p < 0.001). Children with a confirmed impetigo diagnosis exhibited lower mean personal hygiene scores (2.6 ± 0.723) in contrast to those without such diagnoses (3.75 ± 0.911).Conclusion: Socio-demographic factors, including child's gender, parental education level, employment status, and geographic location, emerge as significant determinants of impetigo occurrence. Additionally, there is a strong correlation between proper personal hygiene practices and a reduced incidence of impetigo.Keywords: Staphylococcus pyogenes, Staphylococcus aureus, personal hygiene, skin infections, impetigo